Identifikasi Tingkat Kekotaan dan Faktor-Faktor yang Memengaruhinya di Kawasan Metropolitan Pontianak - Maharani, Sekar Aprilia; Wibisono, Bambang Hari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
The Pontianak Metropolitan Area is part of a provincial strategic area comprising Pontianak City and several districts in Kubu Raya Regency and Mempawah Regency. This study aims to identify the level of urbanization and the factors influencing it within the Pontianak Metropolitan Area. The analysis employs a quantitative method using data normalization, data classification, composite index calculation, and Principal Component Analysis. The variables analyzed include population size, population density, population growth, non-agricultural population, built-up land, socio-economic facilities, and the centrality index. The classification results indicate that the area consists of 22.89% primary villages, 30.12% villages, 36.14% emerging towns, 9.64% small towns, and 1.20% advanced towns. Pontianak City, as the core city, exhibits a higher level of urbanization compared to surrounding areas. Through Principal Component Analysis, two main factors influencing the level of urbanization were identified. The first is the socio-economic factor, which includes variables such as population size, socio-economic facilities, and the centrality index. The second is the demographic and land use factor, encompassing variables such as population density, population growth, non-agricultural population, and built-up land. These findings provide valuable insights into the dynamics of urbanization in the Pontianak Metropolitan Area, serving as a foundation for regional planning and spatial policy-making.